Intercultural relations in Asia : migration and work effectiveness - Leong, Chan-Hoong; Berry, John W., 1939- (World Scientific, 2010)
This book showcases some of the key thematic issues reported by Asian migrants and sojourners residing abroad, as well as non-Asians living in the Far East. The diverse range and scope of the papers demonstrate the interdisciplinary, convoluted and intertwined perspectives in human transnational movement. The book comprises four thematic sections, in Intercultural Relations and Social Integration, cross-national interactions and the notion of rootedness and nation state among individuals and their families form the nexus of discussion. On Cultural Competency in Workplace and Social Environment, the individuals and their performance in the social and corporate spheres take center stage. On one hand, both Asians and non-Asians share similar challenges across cultures, but on the other, they each reported different social and workplace dynamics as a consequence of their ethnic cultural background. In Sociocultural Effectiveness and Emotional Adaptation, the focus gravitates toward socio-emotional adjustment of Asian and Western sojourners in cultures opposite their own. In order to appreciate the cultural and emotive dimensions, discursive examination and comparative analysis across geographic locations are needed. The last thematic category in Understanding Asian Migration in Asia, a ubiquitous challenge in Asian societies will be presented - the rural-urban labor migration movement in China.